Parking utilization pattern of park and ride facility at public transportation terminals - Khalid, Ummi Aqilah; Kadar Hamsa, Abdul Azeez (2013)
Parking utilization survey was administered to examine the parking usage at two existing park and ride facilities along the Kelana Jaya LRT Line. This study also analyses the existing parking supply and its physical conditions through parking space inventory survey at the two selected facilities. Parking characteristics such as parking occupancy, parking accumulation, parking volume, parking turnover and parking duration at each facility were also examined. Findings showed that overall parking utilization pattern at the two facilities was generally high with the occupancy rate of more than 85% (Terminal Putra station) and more than 92% (Kelana Jaya station). Additionally, both stations were found long-term parkers (more than 7 hours). The results from this study were found to be comparable with park and ride studies at Shah Alam and Seremban KTM stations and Washington. Finally, recommendations to improve parking supply to meet increase in parking demand and conclusions are also drawn.